2002
DOI: 10.1053/rapm.2002.30669
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive analgesia: No relevant advantage of preoperative compared with postoperative intravenous administration of morphine, ketamine, and clonidine in patients undergoing transperitoneal tumor nephrectomy☆

Abstract: In contrast to encouraging observations on the combination of antinociceptive drugs, the multireceptor approach tested here failed to exert a clinically relevant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
10
0
2
Order By: Relevance
“…Although several investigators examined preemptive analgesia with systemically administered ketamine in postoperative patients, most reported that systemic ketamine had no preemptive analgesic effect. [31][32][33] These observations are consistent with our results. Immunocytochemical study revealed c-fos protein expression mainly in laminae I-II of the spinal cord two hours after incision of the plantar surface.…”
Section: Effects Of Systemic Ketamine On C-fos Expressionsupporting
confidence: 93%
“…Although several investigators examined preemptive analgesia with systemically administered ketamine in postoperative patients, most reported that systemic ketamine had no preemptive analgesic effect. [31][32][33] These observations are consistent with our results. Immunocytochemical study revealed c-fos protein expression mainly in laminae I-II of the spinal cord two hours after incision of the plantar surface.…”
Section: Effects Of Systemic Ketamine On C-fos Expressionsupporting
confidence: 93%
“…Eine mögliche supportive Wirkung des α 2 -Adrenorezeptor-Agonisten Clonidin in Kombination mit S-(+)-Ketamin zur Schmerzlinderung nach kniechirurgischen Eingriffen scheint sinnvoll zu sein. Derartige Kombinationen wurden stets systemisch oder rückenmarknah eingesetzt [8,10,13], und die Methoden sind seit längerer Zeit bekannt [7,22].…”
Section: Statistikunclassified
“…Após testar várias combinações de morfina e cetamina racêmica em analgesia controlada pelo paciente (ACP) venosa, um estudo verificou que a relação de 1:1 dessa solução promove melhor efeito analgésico e menos efeitos colaterais em pacientes submetidos a cirurgias espinhais ou de quadril 117 . Entretanto, outros estudos não conseguiram demonstrar esse benefício em outros tipos de procedimento cirúrgico [121][122][123] , com uso de R(-) cetamina 124 ou outras doses de cetamina racêmica utilizadas 112,114 . Em crianças, não foi evidenciada potencialização do efeito de opióides com cetamina racêmica por via venosa em apendicectomias 115 , de maneira semelhante a outra pesquisa após amigdalectomia 125 , contrapondo-se ao resultado positivo citado 97 .…”
Section: Estudos Clínicosunclassified
“…Subcutaneous ketamine, however, may cause significant inflammatory reaction at injection site 104 . Intravenous ketamine has been used in bolus 37,105 , bolus followed by continuous infusion 39,62,[106][107][108] , continuous infusion alone or associated to opioid or benzodiazepine 62,[109][110][111][112] and in patient-controlled analgesia PCA) [113][114][115][116][117] . Intravenous racemic ketamine analgesic efficacy depends on infusion dose, on initial dose and on the association of opioids.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation